The Concept of Memorizing Hadith based Cooperative Social at Elementary Islamic School - Malikah, Nurul; Purnama, Medina Nur Asyifah; Sholihah, Abdah Munfaridatus (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
The importance of memorizing hadiths in Islamic elementary schools is able to invite students to remember hadiths permanently for a long time. However, the acquisition of permanent memorization results is only possessed by students who concentrate well when watching the teacher repeat the hadith. This study describes the step of collaborative learning to memorize hadiths to improve memorizing results for all students in the class. This research describes; 1 concept of collaborative learning to improve the ability to memorize hadiths; 2. To explain the steps in collaborative learning memorize the hadith in Islamic elementary school. 3. This research is analyzed based on the research description of the literature review on the principle of cooperation as a social ability and the principle of memorizing as cognitive abilities internalized to facilitate memorizing hadiths without leaving the value of cooperation. The result is that the concept of collaborative learning memorizes hadiths called SRAD GO, namely Seeing, Relating, Associating, Defending and Goal as community learning memorizing group hadiths